Practical guide to diagnostic parasitology / Lynne S. Garcia - Garcia, Lynne Shore
As we move forward into the 21st century, the field of diagnostic medical parasitology continues to see some dramatic changes, including newly recognized pathogens, changing endemicity of familiar pathogens, disease control challenges, geographic and climate changes that support the spread of parasitic disease, new methodologies, expansion of diagnostic testing, and an ongoing review of the approach to and clinical relevance of this type of diagnostic testing on patient care within the managed care environment, as well as the world as a whole. The third edition of the Practical Guide to Diagnostic Parasitology is organized to provide maximum help to the user, particularly from the bench use perspective. New aspects of the field have been addressed in these sections, and many new figures and plates have been added, including extensive color images. Section 1 on the philosophy and approach to diagnostic parasitology has been expanded to include discussions on neglected tropical diseases, the impact of global climate change, population movements, potential outbreak testing, the development of laboratory test menus, and the risk management issues related to "stat" testing. The Section 2 discussion of organism classification and relevant tables has been expanded and updated to provide the user with current information related to changes in nomenclature and overall importance of the various parasite categories to human infection